To Study the Correlation and Analysis between the Transportation and Referral System in Treatment Cases of Drug Dependents or Intoxication (International Journal of Food and Nutritional Sciences, 2022)
The probability of substance use considering 50-50 among general population somehow few are involved in substance use or any means of unfair activities like excessive smoking, tea, coffee and other beverage and use commercial nutrient food, energy drinks and has addiction of any of them but the socially predominate substance used is alcohol. A sample of 30 clinician interview on structured questioner under the study frequently come across the patient using alcohol at variable time line either they use to treat them with minor symptoms but pay less attention on complete cure. The de addiction facilities are supposed to be needed by them.30 interviewed doctors see the patient ranging from 0-40 patient per month of age group 18-65 years.